1989
DOI: 10.4141/cjas89-014
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism and Thermoregulation in the Newborn Calf; Effect of Calving Conditions

Abstract: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
1
4

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 17 publications
7
97
1
4
Order By: Relevance
“…When the animal stands up for the fi rst time and spends 10 min standing, its energy expenditure is also increased by 100%. When it is a bit stronger and is able to stand for more than 30 min, heat production is increased by 40% on average over this period (personal results) [131].…”
Section: Brown Adipose Tissue Metabolism and Thermogenesismentioning
confidence: 99%
“…When the animal stands up for the fi rst time and spends 10 min standing, its energy expenditure is also increased by 100%. When it is a bit stronger and is able to stand for more than 30 min, heat production is increased by 40% on average over this period (personal results) [131].…”
Section: Brown Adipose Tissue Metabolism and Thermogenesismentioning
confidence: 99%
“…Eigenmann et al (1983) and Donovan et al (1986) found that this disorder had a detrimental effect on the level of passive immunity, decreasing the sucking activity. Kasari (1989) and Vermorel at al. (1989) determined that dystocia lowered the concentrations of glucose and NEFA.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, this group revealed the highest levels of glucose and cholesterol. A high level of glucose in the one-day-old calves is evidence of proper acid-base balance and respiratory functions, which in turn account for the fast adaptation of the newborn to the external environment (Kasari, 1989;Vermorel et al, 1989). According to Kurz and Willet (1991), the levels of glucose and cholesterol in calves of that age are associated with the time elapsed between birth and the first ingestion of colostrum.…”
Section: Discussionmentioning
confidence: 99%
“…Vigor, interchangeably used with the word vitality, can be defined as having the capacity to live and grow with physical and mental energy and strength [6]. Reduced newborn calf vigor from dystocia can result from injury, inflammation, inability to maintain homeostasis, as well as from hypoxia and acidosis [1,[7][8][9]. These physiological effects can have behavioral repercussions, such as having reduced motivation to perform natural behaviors for survival, including standing up and suckling colostrum after birth [10].…”
mentioning
confidence: 99%